2014
DOI: 10.1002/j.1556-6978.2014.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Making the Case for Standards of Conduct in Clinical Training

Abstract: The authors examined a proposed set of standards for the personal and professional conduct of counseling trainees. Eighty-two counselor educators and supervisors from programs accredited by the Council for Accreditation of Counseling and Related Educational Programs ranked 55 behaviors divided across 3 categories (i.e., professional, interpersonal, and intrapersonal). Q-sort methodology was used to collect the data, and the results provide a starting point for identifying criteria for gatekeeping practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…A total of 382 participants completed the survey (26% response rate), and respondents with missing or invalid data ( n = 47) were eliminated via listwise deletion (see Sterner, ), leaving a final sample of 335 participants. The response rate for this study was similar to response rates in other studies using counselor educators, which ranged from 19% to 33% (Homrich et al, ; Neukrug, Peterson, Bonner, & Lomas, ; Swank & Smith‐Adcock, ; Warden & Benshoff, ). Frequencies and percentages of the participant demographic variables in this study are reported in Table .…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…A total of 382 participants completed the survey (26% response rate), and respondents with missing or invalid data ( n = 47) were eliminated via listwise deletion (see Sterner, ), leaving a final sample of 335 participants. The response rate for this study was similar to response rates in other studies using counselor educators, which ranged from 19% to 33% (Homrich et al, ; Neukrug, Peterson, Bonner, & Lomas, ; Swank & Smith‐Adcock, ; Warden & Benshoff, ). Frequencies and percentages of the participant demographic variables in this study are reported in Table .…”
Section: Methodssupporting
confidence: 85%
“…Addressing problems of professional competency (PPC) in the counseling profession has received renewed interest in recent years, as illustrated by the number of publications in the Journal of Counseling & Development (Brown, ; Brown‐Rice & Furr, ; Dugger & Francis, ; Herlihy, Hermann, & Greden, ; Ziomek‐Daigle & Christensen, ) and Counselor Education and Supervision (Goodrich & Shin, ; Homrich, DeLorenzi, Bloom, & Godbee, ; Hutchens, Block, & Young, ; Parker et al, ; Rust, Raskin, & Hill, ). Some of this focus may be related to recent court cases that have challenged program expectations for counseling students (see Dugger & Francis, ; Herlihy et al, ; Hutchens et al, ) and to gatekeeping issues in regard to First Amendment rights and the ACA Code of Ethics (American Counseling Association [ACA], ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Credentialing is important to the legitimacy of the counseling profession and the professional stature of counselors (Kaplan et al, 2014). The aim of counselor credentialing is to protect the interests of the public through assuring counselor competence (Homrich, DeLorenzi, Bloom, & Godbee, 2014; Mascari & Webber, 2013; Miller et al, 2010). At the same time, credentials serve as the foundation for establishing expertise in the eyes of the public.…”
Section: Credentialing Of Counselorsmentioning
confidence: 99%
“…Yet because CACREP standards are not specific, several researchers have attempted to define professional competencies in a more detailed format. Homrich, DeLorenzi, Bloom, and Godbee (2014) proposed a set of standards focused on profes-sional and personal conduct, including professional behaviors, interpersonal behaviors, and intrapersonal behaviors. Through a survey of counselor educators in CACREP-accredited programs, Homrich et al (2014) evaluated specific behaviors that could expand upon the current expectations found in the ACA Code of Ethics.…”
mentioning
confidence: 99%